"Team is everything": Reflections on trust, logistics and methodological choices in collaborative interviewing. (10th January 2020) - Schwartz, Ariel E.; Durkin, Brendan
Accessible Summary: People with disabilities often do research. Sometimes, they work together with people with academic training. Sometimes, working together can be challenging. A researcher with academic training and a co‐researcher with a disability worked together to do interviews. This paper is about how we worked together. We talk about how the co‐researcher with a disability got hired, did ethics training and dealt with transportation and his schedule. We also talk about how we worked together to make sure it was easy for him to do the interviews. This paper might help other research teams figure out how to do interviews together. Abstract: Background: People with disabilities are increasingly involved in research. Our understanding of how to support co‐researchers with disabilities has grown since the 1990s. However, research teams have reported challenges in ensuring authentic collaboration. We report on the collaboration between an academic researcher and a co‐researcher with a disability to conduct interviews with other co‐researchers about their experiences in inclusive research. Methods: The academic researcher took fieldnotes throughout the research. Together, she and the co‐researcher audio‐recorded "debriefs" after each interview. The academic researcher reviewed all fieldnotes and transcribed "debriefs." Together, the academic researcher and co‐researcher listened to and reflected on the audio‐recorded debriefs. Results: In this reflective manuscript, we discuss the hiring process, ethics training, logistical challenges and tools we developed to support the co‐researcher in his role. We also discuss challenges, including the academic researcher's difficulty eliciting critical feedback from the co‐researcher. This manuscript includes both the voice of the academic researcher and the co‐researcher. Conclusion: Our research process was supported by our prior relationship, accessible processes, and time for training and reflective practice. We call attention to the importance of establishing trust and methods to elicit critical feedback from co‐researchers. We also discuss logistical challenges and the impact of methodological choices on research collaborations.